Rotenone aggravates PD-like pathology in A53T mutant human α-synuclein transgenic mice in an age-dependent manner - Chen, An-Di; Cao, Jia-Xin; Chen, Hai-Chao; Du, Hong-Li; Xi, Xiao-Xia; Sun, Jing; Yin, Jie; Jing, Yu-Hong; Gao, Li-Ping (Frontiers in Aging Neuroscience, 2022)
Multiple factors such as gene, environment and age, are involved in development of PD pathology. However, how various factors interact to cause PD remains unclear. Here, 3 months and 9 months old hα-syn+/-(A53T) mice were treated with low-dose rotenone for 2 months to explore the mechanisms underline the environment-gene-age interaction in the occurrence of PD. We have examined the behavior of mice and the PD like pathologies of brain and gut.Our present results showed that impairments of the motor function and olfactory function were more serious in old hα-syn+/- mice with rotenone than that of young mice. The loss of the dopaminergic neuron in the SNc are more in old hα-syn+/- mice with rotenone than that of young mice. Expression of hα-syn is increased in the SNc of hα-syn+/- mice following rotenone treatment for 2 months. Furthermore, the number of activated microglia cell increased in SNc and accompanied the high expression of inflammatory cytokines including TNF-α and IL-18 in the midbrain of old hα-syn+/- mice treated with rotenone. Meanwhile, we found that after treatment with rotenone, hα-syn positive particles deposited in the intestinal wall , intestinal microflora and T lymphocyte subtypes of Peyer’s patches changed, and intestinal mucosal permeability increased. What’s more, these phenomena were obviously age-dependent. These findings suggested that rotenone aggravated the PD-like pathologies and affected the brain and gut of human α-syn+/- mice in an age dependent manner.